Conditional aspects of school-home conversations - Tveit, Anne Dorthe (International Journal about Parents in Education, 2023)
The focus of this study is the conditions in which conversations between school and home take place, and the discussion highlights questions such as the following: Are the participants sincere? Do the participants express the truth about the pupils’ school facilities? How does pupil participating impact the conversation? The background for the study is that conversations between school and home should, according to laws and proposals, be characterized by dialogue (1995; 1998a; 1998b), and research results which show that dialogue in these conversations is quite frequently absent (Lidén, 1997; Nordahl, 2000; Nordahl & Sørlie, 1996; Vestre, 1995). Dialogue is understood here as being communicative action as described by Habermas in The Theory of Communicative Action (1984; , 1987). This theory is criticised, however, this is not commented upon in this paper. Certain conditional aspects are tied to the conversation if it is to be considered as communicative action, and the research question is therefore: “What characterizes the conversation between school and home, and how does the conversation coincide in communicative action?” Through studying the participants’ everyday practices and comparing these with communicative action, one may acquire knowledge about how the conversation corresponds with/does not correspond with communicative action, and in this way get insight into the conditional aspects of school-home conversations.